SYNTHESIS AND SPECTROSCOPIC CHARACTERIZATION OF HYBRID MAGNETIC NANOPARTICLES, BASED ON FE@AU AND PYRROLE - SORAN, Maria-Loredana; PANĂ, Ovidiu; NAN, Alexandrina; LEOŞTEAN, Cristian; BRATU, Ioan (Studia Universitatis Babeș-Bolyai Chemia, 2017)
The synthesis and characterization of Fe@Au and Fe@Au covered with pyrrole and pyrrole functionalized with N-succinimide is presented. The synthesis of Fe@Au nanoparticles, with diameters between 5 -7 nm was performed by the reverse micelles method. The hybrid composites Fe@Au nanoparticles covered by the pyrrole copolymer were obtained by chemical oxidative polymerization of a mixture of pyrrole and substituted pyrrole with N-succinimide monomers in water. The properties of these composites were investigated by transmission electron microscopy and FTIR spectroscopy.